Apicomplexan phosphodiesterases in cyclic nucleotide turnover: conservation, function, and therapeutic potential - William J. Moss; Lorenzo Brusini; Ronja Kuehnel; Mathieu Brochet; Kevin M. Brown (mBio, 2024)
ABSTRACT Apicomplexa encompasses a large number of intracellular parasites infecting a wide range of animals. Cyclic nucleotide signaling is crucial for a variety of apicomplexan life stages and cellular processes. The cyclases and kinases that synthesize and respond to cyclic nucleotides (i.e., 3′,5′-cyclic guanosine monophosphate and 3′,5′-cyclic adenosine monophosphate) are highly conserved and essential throughout the parasite phylum. Growing evidence indicates that phosphodiesterases (PDEs) are also critical for regulating cyclic nucleotide signaling via cyclic nucleotide hydrolysis. Here, we discuss recent advances in apicomplexan PDE biology and opportunities for therapeutic interventions, with special emphasis on the major human apicomplexan parasite genera Plasmodium, Toxoplasma, Cryptosporidium, and Babesia. In particular, we show a highly flexible repertoire of apicomplexan PDEs associated with a wide range of cellular requirements across parasites and lifecycle stages. Despite this phylogenetic diversity, cellular requirements of apicomplexan PDEs for motility, host cell egress, or invasion are conserved. However, the molecular wiring of associated PDEs is extremely malleable suggesting that PDE diversity and redundancy are key for the optimization of cyclic nucleotide turnover to respond to the various environments encountered by each parasite and life stage. Understanding how apicomplexan PDEs are regulated and integrating multiple signaling systems into a unified response represent an untapped avenue for future exploration.